PRACTICAL APPLICATION OF LINEAR ALGEBRA IN THE PYTHON PROGRAMMING LANGUAGE - Salikhova V. K.; Eshonkulova F. A.; Habibullayev M. M. (Modern American Journals, 2025)
This article explores the practical applications of linear algebra using the Python programming language, with a focus on its relevance to computer science education in technical universities. Linear algebra plays a crucial role in various domains such as data science, computer graphics, artificial intelligence, and machine learning. The study highlights how Python, with its extensive scientific libraries such as NumPy and SciPy, offers a powerful and accessible environment for solving linear algebra problems. Through examples and explanations, the article demonstrates how students can implement fundamental concepts like matrix operations, vector transformations, and systems of linear equations in Python. The goal is to bridge the gap between abstract mathematical theory and real-world computational practices, thereby enhancing students’ practical skills and readiness for industry demands.
Keywords: linear algebra, Python programming, NumPy, matrix operations, computational mathematics, applied informatics, technical education, machine learning, algorithm design, systems of equations.